Teorie optimálních měnových oblastí v praxi - Bednář, Ondřej (2023)
The dissertation thesis focuses on the practical use of the optimum currency area (OCA) theory. The thesis strives to assess the vast OCA literature and select its most relevant criteria for the contemporary discussion of countries considering joining a currency union. Based on the chosen criteria, the thesis evaluates the Eurozone candidate countries. As is argued, there are two most important criteria. One of them considers the synchronicity of business cycles, industrial structures, and product diversification of the currency union members. This criterion is attributed mainly to work by P. Kenen. The second criterion deals with trade openness and its consequent limitation on monetary policy independence which is based on arguments by R. McKinnon. The thesis empirically researches the latter criterion. In the first empirical analysis, the Mélitz model is applied to the group of Eurozone candidate countries. The model builds on the McKinnon's criterion and extends it with aspects that determine the usefulness of the exchange rate as a tool to impact a country's terms of trade. The second empirical part is a panel data econometric analysis of the candidate countries' real interest rate changes. The research confirms that most of the countries in the Eurozone orbit follow the policy of the ECB. The more a country is financially and capitally integrated with the Eurozone, the more the changes in real interest rates are associated with the changes in the Eurozone. The third empirical analysis examines a rapid and unexpected hike of the Czech hallmark interest rate on the EURCZK exchange rate. The investigation is conducted by constructing a counterfactual prediction of the EURCZK rate for the situation if the CNB would act as the market had expected. The actual exchange rate significantly deviated from the counterfactual one only in the first week after the move, and then it regressed back to the predicted values.